Error Detection Analysis in LoRa Communication in Wireless Sensor Network Implementation with Microcontroller-Based Cyclic Redundancy Check Method - Adzimatunnisa, Khomsanes; Suja’i , Muhammad Syirajuddin; Koesmarijanto , Koesmarijanto (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Wireless sensor networks (WSN) play a vital role in collecting distributed data for various applications, including environmental monitoring and smart city systems. Although WSNs promise great potential, communication challenges are a major obstacle that can hinder the reliability and accuracy of transmitted data. A study published in 2018 by Smith et al. in IEEE Transactions on Wireless Communications highlighted that WSN communications are prone to electromagnetic interference, channel noise, and interference, which can lead to transmission errors and signal degradation. These problems can be overcome by using error detection methods, one of which is the Cyclic Redundancy Check (CRC) method. This study focuses on analysis using the CRC method which works by adding redundant bits to the data to be transmitted. At the receiver, a division polynomial is used to verify data integrity. CRC will be implemented with 3 Arduino UNO R3 microcontrollers acting as senders and receivers. The input entered in this communication is photo information. Testing is carried out with a communication distance between LoRa of around 0 to 100 meters in open environmental conditions. Next, the sending node and receiving node will exchange information data, the exchange of information will be carried out alternately between node 1 and node 2. The CRC method detects data transmission errors in the form of damage to digital images, damage to digital images is image noise. Image noise causes the received image to be imperfect or damaged such as blurry to changes in color from the previous image. This is because the pixels of the damaged image experience varying bit changes, resulting in colors that do not match the damaged image. The results of the MSE value obtained in this study with the smallest value are189.5476437 and the largest is 210.0797583.